2022
DOI: 10.1016/j.aej.2022.01.047
|View full text |Cite
|
Sign up to set email alerts
|

Logistic regression analysis for studying the impact of home quarantine on psychological health during COVID-19 in Saudi Arabia

Abstract: During the Coronavirus disease (COVID-19) period, the world witnessed a complete closure of all aspects of social life, and people must go for home quarantine to limit the spread of Corona virus disease. This study aims to use multiple logistic regression model (MLR) to identify the impact of home quarantine on psychological stability of individuals and its relationship to various factors. Maximum likelihood is used to estimate the parameters of MLR. Hosmer-Lemeshow method and Wald statistic are calculated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“… 50 On the other hand, a study among those quarantined at home found that a high percentage of participants were psychologically stable This was linked to the closeness of family members to each other, the more attention of people to their health, and being interested in self-development. 51 Also, home quarantine was found to reduce the stress on the health system compared to the institutional qurantine. 52 …”
Section: Discussionmentioning
confidence: 99%
“… 50 On the other hand, a study among those quarantined at home found that a high percentage of participants were psychologically stable This was linked to the closeness of family members to each other, the more attention of people to their health, and being interested in self-development. 51 Also, home quarantine was found to reduce the stress on the health system compared to the institutional qurantine. 52 …”
Section: Discussionmentioning
confidence: 99%
“…The analysis employed a 95% confidence Interval (CI) for the level of significance using two‐side The analysis was then continued to multivariate analysis. The regression logistic was applied to test whether all independent variables as predicting factors are associated with anxiety 27,28 . In reporting the analysis, this study followed the SAMPL guidelines and STROBE guidelines for cross‐sectional studies reports (https://www.equator-network.org).…”
Section: Methodsmentioning
confidence: 99%
“…DASS, Depression Anxiety and Stress Scale regression logistic was applied to test whether all independent variables as predicting factors are associated with anxiety. 27,28 In reporting the analysis, this study followed the SAMPL guidelines and STROBE guidelines for cross-sectional studies reports (https://www.equatornetwork.org). This study has been granted the Ethics Approval from the Faculty of Medicine Universitas Muhammadiyah Surakarta.…”
Section: Statistical/data Analysismentioning
confidence: 99%
“…When the dependent variable is dichotomous and the independent variable is continuous, categorical, or both, binary logistic regression is generally used ( Park, 2013 ; Jawa, 2022 ). In this study, a binary logistic regression model was used to examine the effect of independent variables on the dependent variable, as the dependent and independent variables were coded with binary options.…”
Section: Study Methodsmentioning
confidence: 99%